Sarcomatous transformation of florid cemento-osseous dysplasia: a case report - Biswas, Sailendranath; Saha, Anindita; Das, Asish K.; Ganguly, Shreya (International Journal of Research in Medical Sciences, 2024)
Florid cemento-osseous dysplasia (COD) represents a rare group of benign fibro-osseous disorders, while osteogenic sarcoma (OS) on the other hand, is a malignant tumour of ominous prognosis. The malignant transformation of a benign fibro-osseous lesion of the jaw is quite uncommon and has few reported cases. The clinico-radiological findings and histopathological analysis of a lesion present in all four quadrants of the jaw of a patient who reported at the outpatient department of a regional dental college is presented here. The lesion underwent sarcomatous transformation over two months and the findings were confirmed by histopathological evaluation. Although florid cemento-osseous dysplasia is a benign lesion of the jaw with a very low propensity for malignant transformation, it should be closely monitored in patients with tumour predisposition syndromes. Further research and molecular studies are required for better understanding of inadvertent changes.